Endemism and taxonomy of Chaptalia (Asteraceae) in the Caribbean. II. Taxonomic treatmen - Katinas, Liliana (2014)
This is the second part of a revision of the genus Chaptalia (Asteraceae) in the Caribbean Islands, containing a taxonomic treatment. The number of recognized species in the genus is reduced from 31 to two endemics, C. angustata and C. dentata, and two non-en-demics, C. albicans and C. nutans. A morphological analysis led to synonymization of numerous names under C. dentata. A key to the species of Chaptalia in the Caribbean is provided together with species descriptions, illustrations, and distribution maps.